ANALISIS POTENSI EKONOMI DI KABUPATEN MERANGIN - Sudirman Sudirman (Universitas Batanghari Jambi, 2015)
National development in the developing countries in general , focused on economic development through economic growth efforts . Economic growth is closely related to the increased production of goods and services , as measured among others by the Gross Domestic Product ( GDP ) at the national level and the Gross Domestic Product (GDP ) at the local level either provincial , district and city.In economic development , local government and responsible role in improving the standard of living and welfare. Regional economic development is a process in which local governments and communities to manage resources that exist and form a partnership with the private sector to create new jobs and stimulate the development of economic activities in the region.Keyword :gross domestic product (GDP)